2017
DOI: 10.1007/s00392-017-1089-y
|View full text |Cite|
|
Sign up to set email alerts
|

Is there any benefit using low-intensity inspiratory and peripheral muscle training in heart failure? A randomized clinical trial

Abstract: Unfortunately, an incorrect figure was provided in the original manuscript. Figure 1 has to be substituted by Fig. 2. A new Fig. 2 is now provided. The correct Figs. 1 and 2 with according captions are given below. After the NYHA functional class analysis using the McNemar test, the p value is missing in the Results section of the Abstract. The correct text is reproduced below. Results All groups showed similar quality-of-life improvements. Low and moderate intensities training programs improved inspiratory mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 38 publications
1
65
0
6
Order By: Relevance
“…These results are broadly consistent with those of Laoutaris et al, who concluded that improvements in dyspnea and exercise tolerance after and consistent with those of previous studies, which have shown a similar attenuation of remodeling mainly attributed to a decrease in peripheral vascular resistance following aerobic exercise [31]. The results of this study are in agreement with those of previous studies that compared inspiratory muscle training with other modes of training These studies reported that the addition of inspiratory muscle training to aerobic training [13,28] or combined aerobic and resistance training [32] resulted in significant improvements in respiratory muscle strength, functional capacity, and cardiorespiratory responses to exercise in patients with chronic heart failure and inspiratory muscle weakness. [13,28,32] However, our findings are contradicted by those of Weiner et al [33], who failed to achieve a significant improvement in peak exercise oxygen consumption following 3 months of specific inspiratory muscle training, and Adamop-oulos et al, who reported that the addition of inspiratory muscle training to aerobic training gained an additional improvement in respiratory muscle function without significant changes in cardiopulmonary exercise testing [13].…”
Section: Discussionsupporting
confidence: 92%
“…These results are broadly consistent with those of Laoutaris et al, who concluded that improvements in dyspnea and exercise tolerance after and consistent with those of previous studies, which have shown a similar attenuation of remodeling mainly attributed to a decrease in peripheral vascular resistance following aerobic exercise [31]. The results of this study are in agreement with those of previous studies that compared inspiratory muscle training with other modes of training These studies reported that the addition of inspiratory muscle training to aerobic training [13,28] or combined aerobic and resistance training [32] resulted in significant improvements in respiratory muscle strength, functional capacity, and cardiorespiratory responses to exercise in patients with chronic heart failure and inspiratory muscle weakness. [13,28,32] However, our findings are contradicted by those of Weiner et al [33], who failed to achieve a significant improvement in peak exercise oxygen consumption following 3 months of specific inspiratory muscle training, and Adamop-oulos et al, who reported that the addition of inspiratory muscle training to aerobic training gained an additional improvement in respiratory muscle function without significant changes in cardiopulmonary exercise testing [13].…”
Section: Discussionsupporting
confidence: 92%
“…The use of slow breathing (SLOWB) technique has been shown to reduce dyspnoea, improve oxygen saturation and exercise tolerance in HF patients, acutely increase baroreflex gain and stability in patients with CV disease and a risk for sudden death [4245]. Data from pilot studies of patients with systolic chronic HF have demonstrated the feasibility of device-guided SLOWB pacing with the use of the RESPeRATE, improvements in NYHA class and left ventricle ejection fraction (LVEF), reductions in pulmonary pressure [46, 47] and breathlessness [48]. The effects of SLOWB training on blood pressure (BP) in chronic HF has been reported to be marginal with low incidence of orthostatic hypotension [49].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory muscle weakness (MIP <70% of the predicted) (Kawauchi et al, ), was observed in 27 patients (64.28%) in the treatment group and 24 patients (57.14%) in the control group. Over the course of the study, the treatment group had a mean 39.6 ± 6.35% of MIP, but the control group had a fixed 10% of MIP.…”
Section: Resultsmentioning
confidence: 99%
“…While emphasizing the importance of the duration of the intervention, Palau et al () found that a 12‐week IMT program had positive effects on classes III and IV, HF patients with HFpEF. Kawauchi et al () found that only moderate‐intensity IMT improves expiratory muscle strength and the NYHA functional class in classes II and III patients with HF reduced ejection fraction (HFrEF). Given that in the review of literature and the present study, the greatest improvement was observed in classes II and III patients, it can be said with some caution that IMT is effective in improving the NYHA functional class in HFpEF and HFrEF patients; however, this finding requires further studies.…”
Section: Discussionmentioning
confidence: 99%